OPTIMIZATION OF AGROPOLITAN OF EAST JAVA PROVINCE AS AN EFFORT TO RESTORE LOCAL ECONOMY DURING THE COVID 19 PANDEMIC - Taufiq Rahman Ilyas (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2022)
Optimization of agropolitan as an economic recovery effort due to the impact of the Covid-19 pandemic is a strategic step taken by the East Java Provincial Government. Empowerment of agropolitan communities is an option given its position as the spearhead of agricultural commodities. The whole action must all be done through the development of an efficient system. This strategic step includes several things including the following; 1) Maximizing written regulations in strengthening institutions in the agropolitan sector, 2) Expanding cooperation between local governments, centers, financial institutions, SOEs, and all related groups, 3) Diversification of superior products, 4) Marketing Education, 5) Digitalization of marketing, 6) Ease of access to capital. Then the advice that can be given is that the government must be consistent in supporting and providing assistance to agropolitan communities in developing agropolitan areas for the sake of local economic recovery.